2013
DOI: 10.2485/jhtb.22.311
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatibility and Anti-Bacterial Activity of Zn-Containing HA/TiO2 Hybrid Coatings on Ti Substrate

Abstract: Abstract. To improve the osteogenic and anti-bacterial activity for the hydroxyapatite coated titanium substrate Zn containing HA biological coating was prepared on commercially pure Ti via the sol-gel method after treatment by oxidation which produced a porous titania coating on the titanium. The phase structures of the coatings were characterized by X-ray diffraction. The release concentration of zinc was measured by an inductively coupled plasma spectrometer. In vitro co-culture assays were performed to eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 18 publications
1
13
0
Order By: Relevance
“…In accordance with the existing literature, the most common elements used for hydroxyapatite doping are silver and zinc. It is known that silver is used in HAp doping for its antimicrobial properties, while the zinc content can lead also to increased biocompatible properties of the coating, and may contribute to the wound healing process [17,[55][56][57][58][59].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In accordance with the existing literature, the most common elements used for hydroxyapatite doping are silver and zinc. It is known that silver is used in HAp doping for its antimicrobial properties, while the zinc content can lead also to increased biocompatible properties of the coating, and may contribute to the wound healing process [17,[55][56][57][58][59].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Thian et al [32], in their studies on "zinc-substituted hydroxyapatite: a biomaterial with enhanced bioactivity and antimicrobial properties", demonstrated that the presence of Zn 2+ ions in the structure of the hydroxyapatite stimulated the bioactivity of HAp. On the other hand, previous research [32,[55][56][57][58][59] provides information on the antimicrobial activity of ZnHAp against various pathogens. Radovanović et al [33] showed that E. coli, S. aureus, P. aeruginosa, and C. albicans were susceptible to Zn-HA, and the degree of reduction was increased when the zinc ion content increased.…”
Section: Discussionmentioning
confidence: 99%
“…Zinc (Zn 2+ ) ion substitution in biomaterials has been thoroughly investigated, for both its osteogenic [95] and antibacterial activities [96][97][98][99][100][101][102][103][104]. The mechanism of inhibition of microbial growth by zinc ions includes several aspects.…”
Section: Zinc-substituted Hydroxyapatitementioning
confidence: 99%
“…Superior bioactivity and hydrophilicity on the implants' surface are important qualities, which can enhance rapid osseointegration [4] . Scholars have investigated many surface modification methods, including Ti plasma coating, hydroxyapatite coating, micro-arc oxidation, and plasma spraying [5,6,7] . Each method has its advantages and disadvantages according to its materials and processes.…”
mentioning
confidence: 99%